Desiccation and freezing tolerance of embryonic axes and lateral buds of Citrus SPP: implications for germplasm conservation - Santos, Izulmé R. I., author; Stushnoff, Cecil, advisor (Colorado State University. Libraries, 1999)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Citrus fruits -- Germplasm resources; Citrus fruits -- Drought tolerance; Citrus fruits -- Frost resistance